(untitled) (International Journal of Engineering and Computer Science, 2020)
This study focuses on the aspects of securing financial transaction data through encryption and other forms of encryption. The most recommended ones are AES-256-GCM encryption and its application towards having data integrity and confidentiality at the time of transmission. The study describes the threat involved in the transfer and storage concerning financial data. Combining with secure transport protocols shows the clear way in which AES-256-GCM encryption would protect other types of sensitive data, such as through IPsec VPN tunnels. Both management services and the market are dependent on data technologies, since new forms of services and facilities are being developed with each single device. Some of the challenges associated with this area were given as performance overhead due to encryption, and the system’s inability to scale to accommodate large amounts of financial data. However, with this method, it has taken care of the industry-standard compliance aspects, making it, thereby, a formidable ground in the security of financial transactions in the digital environment. The results obtained from As shown in the graph, the increase in plaintext size (P_size) correlates with the increase in AES-256-GCM encryption time (T_encryption), which goes from about 20 ms for 1 MB to over 120 ms for 20 MB, indicating that more and more computational work is required to encrypt such a large data file. In the meantime, the security (S_encryption) of the encrypted data-which is graphically represented by the blue line-increases immensely when the Data size becomes larger. On the contrary, the red line, which refers to that of unencrypted data, remains static to illustrate the low security level. Thus, encryption becomes necessary to secure sensitive data as it grows in size.